(untitled) (IJM: Journal of Multidisiplinary, 2025)
Uric acid is a waste product resulting from the metabolism of purines. Excess production or impaired excretion of uric acid can lead to elevated uric acid levels. Elderly individuals are particularly vulnerable to increased uric acid levels due to declining organ function or metabolic processes, as well as the consumption of purine-rich foods. This used method with a case study approach to nursing care, including reviewing, est ablishing diagnosis, planning, implementing, and evaluating. Purpose: This case study described the nursing care provided to an elderly patient with elevated uric acid levels in Gampong Peunayong. Ny.R has experienced elevated uric acid levels for the past six years, with a recent level of 10.2 mg/dL. She reported pain in both knees radiating to the calves, with a pain score of 4 on the Numeric Rating Scale (NRS). The nursing interventions for the diagnosis of chronic pain included pain management education and warm compresses using boiled ginger water. For the diagnosis of ineffective health management, interventions included education on the concept of uric acid, a low-purine diet, and joint stretching exercises. For the risk of falling diagnosis, fall prevention education and Otago strength and balance exercises were implemented. After the intervention there was an increase in the patient’s knowledge, a decrease in uric acid levels from 10.2 mg/dL to 8.7 mg/dL, and a reduction in pain intensity from an NRS score of 4 to 2.